Meningkatkan Kinerja Karyawan Logistik melalui Self-Efficacy dan Prosocial Motivation : Analisis Mediasi Work Engagement di Surakarta - Rohmawan Adi Pratama; Purwati Purwati; Indah Novita Sari; Filda Khoirun Nikmah (Universitas Veteran Bangun Nusantara, 2025)
This study aims to examine the impact of self-efficacy and prosocial motivation on employee performance in the logistics sector in Surakarta, with a particular focus on the mediating role of work engagement. This empirical quantitative study surveyed 110 respondents and used SEM-PLS to examine how self-efficacy and prosocial motivation directly affect work engagement and employee performance, including work engagement’s mediating role. The findings show that self-efficacy positively impacts both work engagement and employee performance. Likewise, prosocial motivation significantly boosts work engagement and performance. Work engagement stands out as the strongest predictor of performance and plays a key mediating role between self-efficacy, prosocial motivation, and performance. Therefore, strengthening employees’ confidence and prosocial motivation enhances work engagement, which ultimately improves performance in the fast-paced logistics sector.